APPLICATIONS OF THE TEACHING FILM IN ACADEMIC LEARNING, FOR PRACTICAL SKILLS TRAINING - CORNELIA STAN (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. The modern teacher achieves his goals with the support of many ways of learning, ever newer and more sophisticated (multimedia support, online transmission techniques, teaching materials based on new information and communication technologies). Thus, current educational programs focus on developing management skills of experiential learning and the formation of cognitive structures that emphasize the need for procedural knowledge acquisition through flexible transmission techniques that highlight information in training at any level.